Peggy Bowen Leight, 1957. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 11-3-57 p.D1.
Peggy Bowen Leight, 1957.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth